2005
DOI: 10.1016/j.ejcts.2005.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of predictors of late stroke after total aortic arch repair

Abstract: Objective: The number of aortic surgeries has recently increased, with improvement of outcome due to the development of various novel operative techniques and adjuncts. Although the postoperative incidence of stroke, the most severe complication of aortic surgery, is still a matter of concern and has been described well previously, late stroke after aortic arch repair has not been described well. We assessed the incidence and predictors of late stroke after total aortic arch repair. Methods: From January 1993 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…AF was reported to occur in almost 50 % of patients after major cardiovascular surgeries such as total arch replacement and was higher in these patients than in those with other cardiovascular surgeries such as valve replacement and CABG [ 20 , 21 ]. It was also reported that the occurrence of AF after such major surgeries peaked on day 2, and about half was widely distributed as well after day 3 [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…AF was reported to occur in almost 50 % of patients after major cardiovascular surgeries such as total arch replacement and was higher in these patients than in those with other cardiovascular surgeries such as valve replacement and CABG [ 20 , 21 ]. It was also reported that the occurrence of AF after such major surgeries peaked on day 2, and about half was widely distributed as well after day 3 [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…No further analysis of neurological defects following TAR, such as stroke or paraplegia until hospital discharge, was carried out in this cohort study owning to their lower incidence (2.1, 3.4%, respectively). Previous investigations provided robust evidence that stroke primarily occurred in patients with concomitant coronary artery bypass grafting, cerebrovascular defect history, or new-set atrial fibrillation [34, 35]. Surgical techniques, including hypothermic circulatory arrest times, selective antegrade cerebral temperature [36, 37], unilateral or bilateral cerebral perfusion [38] and treatment for distal aortic arch aneurysm [19], also significantly contribute to stroke development.…”
Section: Discussionmentioning
confidence: 99%